Towards Future Technologies for Business Ecosystem Innovation - Prasad, Ramjee; Ligthart, L. P. (River Publishers series in communications., 2018)
Towards future technologies for business ecosystem innovation describes CONASENSE within the broad platform of the CTIF Global Capsule (CGC) covering future technologies and its enablers, smart cities, telemedicine, crowd computing, satellite, unmanned air vehicles, cooperative wireless sensor network, remotely piloted aircraft system, network neutrality as well as virtual business model.